Pandemic grief in El Salvador: factors that predict dysfunctional grief due to a COVID-19 death among Salvadoran adults - Lobos-Rivera, Marlon Elías (2023)
Thousands of people have died of COVID-19 in El Salvador. However, little is known about the mental health of those who are mourning the loss of a loved one to COVID-19. Therefore, the objective of this study was to examine the dysfunctional grief associated with COVID-19 death among Salvadoran adults. A sample of 435 Salvadorans (M = 29 years; SD = 8.75) who lost a family member or loved one to COVID-19 completed a digital survey using the Google Forms platform, during April 2 and 28, 2022. The results revealed that 35.1% reported clinically elevated symptoms of dysfunctional grief and among those mourners, and 25.1% also exhibited clinical levels of coronavirus anxiety. A binary logistic regression revealed that predictor variables such as COVID-19 anxiety (p = .003), depression (p = .021), and COVID-19 obsession (p = .032) were significant (χ2 = 84.31; Nagelkerke R2 = .242) and predict a 24.2% chance of dysfunctional bereavement.